Anxiety levels among patients treated with chemotherapy at the Oncology Teaching Hospital in Baghdad city: Anxiety among patients with chemotherapy - kadham Hussin, batool (Iraqi Journal of Cancer and Medical Genetics, 2025)
Chemotherapy may cause psychological effects such as anxiety, and the level of anxiety varies from one person to another. Objective: This study aimed to assess the level of anxiety in patients treated with chemotherapy and to determine the relationships between anxiety levels and several variables, such as age and sex, level of education, and marital status. Method: A cross-sectional study was conducted from December 2022 to February 2023 at the Oncology Teaching Hospital in Baghdad city; the study involved 65 patients on the morning shift, and a questionnaire was used to measure anxiety levels (Anxiety Self-Rating Scale). The collected data were analyzed via SPSS V.23, which included descriptive statistical tests, frequencies, percentages, means, and chi-square tests for inferential analysis. Results: The results indicated that the majority of participants were women. (58.5%), aged between 39 and 48 years (30.8%) and diagnosed with breast cancer (41.5%). The highest percentages of anxiety (55.4%, 32.3%, and 12.3%) were moderate, mild, and extreme, respectively. Furthermore, the chi-square test revealed no statistically significant relationship between anxiety level and participants› demographic variables. Conclusion: This study revealed that patients had a moderate level of anxiety. There was no significant relationship between the level of anxiety of patients treated with chemotherapy and their demographic characteristics.